Organotin Compound Derived from 3-Hydroxy-2-formylpyridine Semicarbazone: Synthesis, Crystal Structure, and Antiproliferative Activity. (12th May 2010) - Wiecek, Joanna; Kovala-Demertzi, Dimitra; Ciunik, Zbigniew; Wietrzyk, Joanna; Zervou, Maria; Demertzis, Mavroudis A.
Abstract : The novel diphenyltin(IV) compound [ Ph 2 ( HyFoSc ) Sn ] (2 ), where H 2 HyFoSc (1 ) is 3-hydroxy-2-formylpyridine semicarbazone, was prepared and characterized by vibrational and NMR ( 1 H, 13 C) spectroscopy. The structure of [Ph 2 (HyFoSc)Sn] was confirmed by single-crystal X-ray crystallography. The doubly deprotonated ligand is coordinated to the tin atom through the enolic-oxygen, the azomethine-nitrogen, and phenolic-oxygen, and so acts as an anionic tridentate ligand with the ONO donors. Two carbon atoms complete the fivefold coordination at the tin(IV) center. Intermolecular hydrogen bonding, C–H → π, and π → π interactions combine to stabilize the crystal structure. Compounds 1 and 2 have been evaluated for antiproliferative activity in vitro against the cells of three human tumor cell lines: MCF-7 (human breast cancer cell line), T24 (bladder cancer cell line), A549 (nonsmall cell lung carcinoma), and a mouse fibroblast L-929 cancer cell line.